Using biomonitors to evaluate soil and air pollution by natural radionuclides in thermal power plant and coal mining areas - Galhardi, Juliana A.; Bonotto, Daniel M. [UNESP]; García-Tenorio, Rafael; Francés, Inmaculada D.; Motta, João G. (My University, 2017)
Coal-fired power plants and coal mining are sources of soil and air pollution by radionuclides, as fossil fuels may contain natural levels of toxic and radioactive elements. For the evaluation of air and soil pollution by natural radionuclides in coal industry areas, plants have been proposed as biomonitors. In tropical areas, the transfer of radionuclides from soil/air to plants has been less investigated. In order to contribute for understanding the transfer processes of radionuclides from soil and air to plants in tropical areas affected by coal mining and burning, the absorption of 234U, 238U and 210Po by ferns, lichens, mosses, soybean, wheat, pine and eucalyptus cultivated around a coal-fired power plant and coal mining area in southern Brazil was evaluated. Samples of plants, cultivated soil, coal and coal ash were prepared at LABIDRO (Isotopes and Hydrochemistry Laboratory), UNESP, Rio Claro (SP), Brazil. Alphaspectrometry was performed at Applied Nuclear Physics Laboratories, University of Seville, Seville, Spain. It was found that deviations from the natural U isotopic ratios were recorded at all investigated area for all the group of samples, which indicate possible industrial and mining sources of U for the vegetables. In some cases, the transfer factors of radionuclides from soil to the vegetables exceeded the limit proposed by International Atomic Energy Agency, which can indicate that the mining and the thermal power plant activities represent considerable environmental risks in the investigated area. Mosses seem to be more sensitive as a biomonitor for air pollution, followed by lichens and ferns. Particulate emissions from the coal-fired power plant are the most probable U-source in the region and the results obtained through the biomonitoring are comparable to those found in other regions, confirming the effectiveness of the plant species as biomonitors of the air quality in the investigated area. Their use can provide information about the pollutants concentration in the environment, also elucidating the ecological consequences of the air pollution, especially in tropical areas, where important industrial, mining and agricultural activities take place, being responsible by the release into the atmosphere of considerable amounts of radionuclides.
Keywords: Biomonitoring; Coal mine; Lichen; Moss; Thermal power plant; Vegetables